(untitled) (Periphērica, 2020)
Abstract: Since its inception in 1991, the Cine-Lit film conference, sponsored by multiple Oregon universities, in conjunction with the Portland International Film Festival, has climaxed with the Directors Round Table of invitees, all auteurs, from Spain and Latin America after several days of screenings of films from these geographical areas and the presentation of academic papers. At Cine-Lit 8 (2015), we were fortunate to attend one of the best Directors Round Tables ever. Below the reader will find a translation of that conversation with six directors about problems of globalization, film financing in their countries and the local as well as the international distribution of their films.